(untitled) (VETERINARIA, 2020)
Based on the criteria we find relevant and with maximum objectivity we assess the index of well-being of the three animal categories. Selected criteria include territoriality, diet, reproduction, social status and the possibility of expressing natural behavior. Each criterion is scored from 1 to 10. It is evident that the maximum index of well-being (50) is allocated to stray animals, and the lowest (17-20) to pets. Between these two categories are farm animals with the index ranging from 21 - 25. In the worst position are pets who, by humans, are not considered to be sources of material gain but rather stand on the other end of emotional relationship. According to relevant criteria, limitations imposed on pets are usually more senseless then production and technologyrelated limitations to farm animals. As social interactions take place primarily at the level of individuals of different and not of the same species, human attitudes and not naturally behaved same-species animals have strong influence on behavior of pets. Sometimes, as a natural consequence, various ethological issues are created to additionally affect pets’ welfare.